Colonialism’s Legacy and Impact on Forest Ecosystems: Case Studies in Brazil and the Democratic Republic of Congo - Dabees, Mai (European Journal of Sustainable Development, 2025)
The deforestation of the Amazon rainforest in Brazil and the illegal copper and cobalt mines in the Democratic Republic of Congo (DRC) are two of the direst environmental crises of the 21st century. Through a historical analysis, this paper determines how the colonial histories of both countries affect the modern-day policy and economic choices that exacerbate these crises. This paper finds that institutions put in place by European powers during colonialism remain and continue to determine the role of both countries in the international political economy. Brazil’s government continues the conquest of the Amazon and extermination of indigenous communities that began under Portugal in pursuit of economic exploits, and the DRC continues to rely on foreign-owned mines within the country and the export of minerals to support itself. This aligns with the theory of path dependency by indicating that colonial powers determine a country’s long-term roles in the global economy long after independence. Keywords: environmental sustainability, socioeconomics, developing countries, global environmental policy, deforestation, colonialism, neocolonialism